A method for improving the high conductivity of magnesium-aluminum alloy wire
By optimizing the raw material composition and processing technology of magnesium-aluminum alloy wire, including smelting, refining, extrusion, cold drawing and impregnation, the problem of coordinating the conductivity and high-temperature creep of magnesium-aluminum alloy wire was solved, and the stability and performance under acid corrosion conditions were improved.
Patent Information
- Application Number
- CN202311033142.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The conductivity and high-temperature creep of existing magnesium-aluminum alloy wires are difficult to improve in a coordinated manner, and their performance stability is poor under acid corrosion conditions, which limits their application efficiency.
Using Mg, Cr, Si, Ti and modification modifiers in specific proportions as raw materials, the alloy microstructure and interfacial activity are optimized through smelting, refining, extrusion and cold drawing, combined with hot modification by modification modifiers and impregnation treatment in soaking solution, thereby improving electrical conductivity and high-temperature creep performance.
It significantly improves the conductivity and high-temperature creep performance of magnesium-aluminum alloy wires, and maintains stability under acid corrosion conditions, thus comprehensively improving the overall performance of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy wire technology, and more specifically to a method for improving the conductivity of magnesium-aluminum alloy wire. Background Technology
[0002] Magnesium-aluminum alloy is a metallic material with very low density, currently used in handheld electronic devices, automobiles, aerospace, and other fields. However, existing magnesium-aluminum alloy wires use relatively conventional raw materials and have simple manufacturing processes. It is difficult to coordinate and improve the conductivity and high-temperature creep resistance of the wires, and the products have poor performance stability under acid corrosion conditions, further limiting the efficiency of product use. Based on this, the present invention provides further improvements. Summary of the Invention
[0003] In view of the deficiencies of the prior art, the purpose of this invention is to provide a method for improving the high conductivity of magnesium-aluminum alloy wires, so as to solve the problems mentioned in the background art.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] This invention provides a method for improving the high conductivity of magnesium-aluminum alloy wire, comprising the following steps:
[0006] Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.2~3.5%, Cr 0.04~0.06%, Si 0.03~0.04%, Ti 0.10~0.15%, modification modifier 0.10~0.20%, and the balance is Al;
[0007] Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for 10-20 minutes to obtain the molten liquid.
[0008] Step 3: The molten liquid from Step 2 is refined for 5-10 minutes using a refining gas composed of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:1. The gas flow rate is 1.2-1.4 cubic meters per minute, and the pressure is 0.12-0.13 atm to obtain the refined liquid.
[0009] Step 4: The refining liquid is cast using an upward drawing method. The upward drawing speed of the aluminum rod is 220~230mm / min, and the diameter of the upward drawing aluminum rod is 30~32mm.
[0010] Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm;
[0011] Step Six: The wire blank is then cold-drawn at a deformation rate of 40%. Upon completion of this process, the magnesium-aluminum alloy wire is obtained. The method for preparing the modification modifier is as follows:
[0012] S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of (4~6):1. Then, the mixture is first heat-treated at 210~220℃ for 5~10 min, and then cooled to 48℃ at a rate of 2~5℃ / min. The mixture is then kept at this temperature for later use to obtain the heat-modified compound.
[0013] SO2: Add 3-5 parts of citric acid and 2-4 parts of sodium sulfate (6% by mass) to 10-15 parts of deionized water, then add 1-2 parts of silane coupling agent KH560 and 0.45-0.55 parts of organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry;
[0014] S03: Subsequently, 10-15% of the total amount of the heat-modified compound is added to the ball milling slurry to adjust the ball milling modification treatment. After the treatment is completed, the mixture is washed with water and dried to obtain the deterioration regulator. The specific operation method of the heat-effect improvement treatment is as follows:
[0015] First, heat the aluminum rod to 210-220℃ at a rate of 1-3℃ / min and hold for 10-15 minutes. Then, heat it to 350℃ at a rate of 3-5℃ / min and hold for 5 minutes. Next, cool it to 165-175℃ at a rate of 2-4℃ / min. Finally, cool it to room temperature at a rate of 1-2℃ / min.
[0016] Preferably, the ball milling speed for the ball milling modification treatment is adjusted to 1000~1500 r / min, and the ball milling time is 1~2 h.
[0017] Preferably, the organic alcohol amine is one or more of triethanolamine, diethanolamine, and ethanolamine.
[0018] Preferably, the wire blank is further subjected to an impregnation and improvement treatment with an impregnation solution before the subsequent cold drawing process;
[0019] The specific operating steps are as follows:
[0020] S11: Prepare a sodium silicate solution with a mass fraction of 10-15% by first mixing sodium silicate and deionized water;
[0021] S12: Add 4-6 parts of sodium silicate solution to 15-20 parts of 5% chitosan solution, then add 2-3 parts of sodium nitrate and 1-2 parts of phosphoric acid solution, stir well to obtain the base agent;
[0022] S13: Add 5-9 parts of sheet graphene and hydroxyapatite agent and 2-5 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution;
[0023] S14: Pass the wire rod through the impregnation solution at a speed of 0.4~0.6m / min, and impregnate it in the impregnation solution at a pressure of 10~20MPa and a temperature of 65~68℃. After impregnation, dry it at 55~60℃ for 30~40min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
[0024] Preferably, the phosphoric acid solution has a mass fraction of 5-8%.
[0025] Preferably, the preparation method of the sheet-like graphene-modified hydroxyapatite agent is as follows:
[0026] The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature.
[0027] Add 3-5 parts of carboxymethyl cellulose to 10-15 parts of ethanol solvent, then add 6-8 parts of hydroxyapatite, 2-5 parts of silica sol and 1-2 parts of tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite regulator.
[0028] Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 and ball milled at a speed of 1000 r / min for 1-2 hours. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
[0029] Preferably, the heat treatment conditions are heat treatment at 260~270℃ for 20~30 minutes.
[0030] Preferably, in step five, the extrusion is carried out at an extrusion temperature of 380~390°C and an extrusion speed of 0.03~0.05mm / s.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. In the improvement of magnesium-aluminum alloy wire of this invention, the raw materials are first optimized and modified. Mg, Cr, Si, Ti and Al are used as the base raw materials. By adding a modification modifier and improving the smelting process, the modification modifier can optimize the activity of the raw materials, improve the microscopic activity of the alloy structure, optimize the internal structure uniformity, refine the grains, and improve the conductivity and high-temperature creep performance of the system. The performance of both is improved in a coordinated manner. At the same time, the product performance is further improved by refining with refining gas. Through thermal efficiency improvement treatment, the microstructure is further improved by thermal homogenization, the grain activity is further improved, and the microstructure uniformity is improved. In addition, the conductivity and high-temperature creep performance of the product are improved in a coordinated manner, and the acid corrosion resistance of the product is further improved. Through the coordination and synergy between thermal efficiency improvement treatment and immersion solution wetting process, the performance of the product is significantly improved.
[0033] 2. The modification modifier uses lanthanum trioxide and cerium oxide compounded and thermally modified to optimize the activity of the raw materials. It is coordinated and harmonized with citric acid, sodium sulfate, silane coupling agent KH560 and organic alcohol amine. The prepared conditioning ball milling fluid is combined with thermally modified compound and ball milling modification to optimize the interfacial system of lanthanum trioxide and cerium oxide. Thus, the modification modifier in the alloy system can better optimize the activity of the raw materials, refine the microstructure and improve the performance of the product.
[0034] 3. Thermal Activation Improvement Treatment: The temperature is increased to 210-220℃ at a rate of 1-3℃ / min and held for 10-15min. Then, the temperature is increased to 350℃ at a rate of 3-5℃ / min and held for 5min. The temperature is then cooled to 165-175℃ at a rate of 2-4℃ / min and finally cooled to room temperature at a rate of 1-2℃ / min. Through two-stage heating and thermal activation followed by staged cooling, and through multi-stage heating-cooling combined steps, the activity and homogenization of the microstructure are optimized, thereby further optimizing the performance of the drawn product during the fiber drawing process.
[0035] 4. The thermal efficiency improvement treatment is combined with the impregnation improvement treatment. The two work synergistically to significantly improve the product's performance. The impregnation improvement treatment uses sodium silicate solution, chitosan solution, sodium nitrate and phosphoric acid solution to form a base agent. The base agent has permeability and stability, which can better penetrate and improve the surface of the billet under high pressure, and optimize the activity of the interface. At the same time, the addition of sheet graphene and hydroxyapatite agent and sodium dodecylbenzenesulfonate work together with the base agent to form the impregnation solution. The sheet graphene and hydroxyapatite agent can better support the raw materials of the impregnation solution, thus optimizing the billet.
[0036] 5. The sheet graphene-hydroxyapatite agent is made by activating sheet graphene with hydrochloric acid solution and co-blending it with carboxymethyl cellulose, hydroxyapatite, silica sol and tetrabutyl titanate. Ball milling optimizes the sheet graphene, improving its activity and load-bearing capacity. The optimized sheet graphene-hydroxyapatite agent can better cooperate with the impregnation solution to work synergistically and improve the performance of the alloy wire. Detailed Implementation
[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] This embodiment provides a method for improving the high conductivity of magnesium-aluminum alloy wire, comprising the following steps:
[0039] Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.2~3.5%, Cr 0.04~0.06%, Si 0.03~0.04%, Ti 0.10~0.15%, modification modifier 0.10~0.20%, and the balance is Al;
[0040] Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for 10-20 minutes to obtain the molten liquid.
[0041] Step 3: The molten liquid from Step 2 is refined for 5-10 minutes using a refining gas composed of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:1. The gas flow rate is 1.2-1.4 cubic meters per minute, and the pressure is 0.12-0.13 atm to obtain the refined liquid.
[0042] Step 4: The refining liquid is cast using an upward drawing method. The upward drawing speed of the aluminum rod is 220~230mm / min, and the diameter of the upward drawing aluminum rod is 30~32mm.
[0043] Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm;
[0044] Step 6: The wire blank is then cold-drawn at a deformation rate of 40%. After the process is completed, magnesium-aluminum alloy wire is obtained.
[0045] The preparation method of the deterioration regulator in this embodiment is as follows:
[0046] S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of (4~6):1. Then, the mixture is first heat-treated at 210~220℃ for 5~10 min, and then cooled to 48℃ at a rate of 2~5℃ / min. The mixture is then kept at this temperature for later use to obtain the heat-modified compound.
[0047] SO2: Add 3-5 parts of citric acid and 2-4 parts of sodium sulfate (6% by mass) to 10-15 parts of deionized water, then add 1-2 parts of silane coupling agent and 0.45-0.55 parts of organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry;
[0048] S03: Subsequently, 10-15% of the total amount of the heat-modified compound is added to the ball milling fluid to adjust the ball milling modification treatment. After the treatment is completed, the mixture is washed with water and dried to obtain the deterioration regulator.
[0049] In this embodiment, the ball milling speed for the ball milling modification treatment is 1000~1500 r / min, and the ball milling time is 1~2 h.
[0050] The organic alcohol amine in this embodiment is one or more combinations of triethanolamine, diethanolamine, and ethanolamine.
[0051] The specific operation method for the thermal efficiency improvement treatment in this embodiment is as follows:
[0052] First, heat the aluminum rod to 210-220℃ at a rate of 1-3℃ / min and hold for 10-15 minutes. Then, heat it to 350℃ at a rate of 3-5℃ / min and hold for 5 minutes. Next, cool it to 165-175℃ at a rate of 2-4℃ / min. Finally, cool it to room temperature at a rate of 1-2℃ / min.
[0053] In this embodiment, the wire blank is further treated with an impregnation solution before cold drawing;
[0054] The specific operating steps are as follows:
[0055] S11: Prepare a sodium silicate solution with a mass fraction of 10-15% by first mixing sodium silicate and deionized water;
[0056] S12: Add 4-6 parts of sodium silicate solution to 15-20 parts of 5% chitosan solution, then add 2-3 parts of sodium nitrate and 1-2 parts of phosphoric acid solution, stir well to obtain the base agent;
[0057] S13: Add 5-9 parts of sheet graphene and hydroxyapatite agent and 2-5 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution;
[0058] S14: Pass the wire rod through the impregnation solution at a speed of 0.4~0.6m / min, and impregnate it in the impregnation solution at a pressure of 10~20MPa and a temperature of 65~68℃. After impregnation, dry it at 55~60℃ for 30~40min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
[0059] The phosphoric acid solution in this embodiment has a mass fraction of 5-8%.
[0060] The preparation method of the sheet-like graphene-modified hydroxyapatite agent in this embodiment is as follows:
[0061] The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature.
[0062] Add 3-5 parts of carboxymethyl cellulose to 10-15 parts of ethanol solvent, then add 6-8 parts of hydroxyapatite, 2-5 parts of silica sol and 1-2 parts of tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite regulator.
[0063] Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 and ball milled at a speed of 1000 r / min for 1-2 hours. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
[0064] The heat treatment conditions in this embodiment are: heat treatment at 260~270℃ for 20~30 minutes.
[0065] In step five of this embodiment, the extrusion is carried out at an extrusion temperature of 380~390°C and an extrusion speed of 0.03~0.05mm / s.
[0066] Example 1.
[0067] This embodiment provides a method for improving the high conductivity of magnesium-aluminum alloy wire, comprising the following steps:
[0068] Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.2%, Cr 0.04%, Si 0.03%, Ti 0.10%, modification modifier 0.10%, and the balance is Al;
[0069] Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for 10 minutes to obtain the molten liquid.
[0070] Step 3: The molten liquid from Step 2 is refined for 5 minutes using a refining gas consisting of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:1. The gas flow rate is 1.2 cubic meters per minute and the pressure is 0.12 atm to obtain the refined liquid.
[0071] Step 4: The refining liquid is cast using an upward drawing method. The upward drawing speed of the aluminum rod is 220 mm / min, and the diameter of the upward drawing aluminum rod is 30 mm.
[0072] Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm;
[0073] Step 6: The wire blank is then cold-drawn at a deformation rate of 40%. After the process is completed, magnesium-aluminum alloy wire is obtained.
[0074] The preparation method of the deterioration regulator in this embodiment is as follows:
[0075] S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of 4:1, and then the mixture is first heat-treated at 210℃ for 5 minutes. After that, it is cooled to 48℃ at a rate of 2℃ / min, kept at the temperature, and then set aside to obtain the heat-modified compound agent.
[0076] S02: Add 3 parts citric acid and 2 parts sodium sulfate (6% by mass) to 10 parts deionized water, then add 1 part silane coupling agent KH560 and 0.45 parts organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry;
[0077] S03: Subsequently, 10% of the total amount of the thermally modified compound is added to the ball milling fluid to adjust the ball milling modification treatment. After the treatment is completed, the mixture is washed with water and dried to obtain the deterioration regulator.
[0078] In this embodiment, the ball milling speed for the ball milling modification treatment is 1000 r / min, and the ball milling time is 1 h.
[0079] In this embodiment, the silane coupling agent is silane coupling agent KH560; the organic alcohol amine is triethanolamine.
[0080] The specific operation method for the thermal efficiency improvement treatment in this embodiment is as follows:
[0081] The aluminum rod is first heated to 210℃ at a rate of 1℃ / min and held for 10 minutes. Then it is heated to 350℃ at a rate of 3℃ / min and held for 5 minutes. Next, it is cooled to 165℃ at a rate of 2℃ / min and finally cooled to room temperature at a rate of 1℃ / min.
[0082] In this embodiment, the wire blank is further treated with an impregnation solution before cold drawing;
[0083] The specific operating steps are as follows:
[0084] S11: Prepare a sodium silicate solution with a mass fraction of 10% by first mixing sodium silicate and deionized water.
[0085] S12: Add 4 parts of sodium silicate solution to 15 parts of chitosan solution with a mass fraction of 5%, then add 2 parts of sodium nitrate and 1 part of phosphoric acid solution, stir well to obtain the base agent;
[0086] S13: Add 5 parts of sheet graphene and hydroxyapatite agent and 2 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution;
[0087] S14: Pass the wire rod through the impregnation solution at a speed of 0.4 m / min. The wire rod is impregnated in the impregnation solution at a pressure of 10 MPa and a temperature of 65°C. After impregnation, dry the wire rod at 55°C for 30 min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
[0088] The phosphoric acid solution in this embodiment has a mass fraction of 5%.
[0089] The preparation method of the sheet-like graphene-modified hydroxyapatite agent in this embodiment is as follows:
[0090] The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature.
[0091] Add 3 parts carboxymethyl cellulose to 10 parts ethanol solvent, then add 6 parts hydroxyapatite, 2 parts silica sol and 1 part tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite regulator.
[0092] Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 for ball milling at a speed of 1000 r / min for 1 hour. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
[0093] The heat treatment conditions in this embodiment are: heat treatment at 260°C for 20 minutes.
[0094] In step five of this embodiment, the extrusion is carried out at an extrusion temperature of 380°C and an extrusion speed of 0.03 mm / s.
[0095] Example 2.
[0096] This embodiment provides a method for improving the high conductivity of magnesium-aluminum alloy wire, comprising the following steps:
[0097] Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.5%, Cr 0.06%, Si 0.04%, Ti 0.15%, modification modifier 0.20%, and the balance is Al;
[0098] Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for 20 minutes to obtain the molten liquid.
[0099] Step 3: The molten liquid from Step 2 is refined for 10 minutes using a refining gas composed of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:1. The gas flow rate is 1.4 cubic meters per minute and the pressure is 0.13 atm to obtain the refined liquid.
[0100] Step 4: The refining liquid is cast using an upward drawing method. The upward drawing speed of the aluminum rod is 230 mm / min, and the diameter of the upward drawing aluminum rod is 32 mm.
[0101] Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm;
[0102] Step 6: The wire blank is then cold-drawn at a deformation rate of 40%. After the process is completed, magnesium-aluminum alloy wire is obtained.
[0103] The preparation method of the deterioration regulator in this embodiment is as follows:
[0104] S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of 6:1, and then the mixture is first heat-treated at 220°C for 10 min, and then cooled to 48°C at a rate of 5°C / min, kept at the temperature, and then set aside to obtain the heat-modified compound agent.
[0105] S02: Add 5 parts citric acid and 4 parts sodium sulfate (6% by mass) to 15 parts deionized water, then add 2 parts silane coupling agent KH560 and 0.55 parts organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry;
[0106] S03: Subsequently, 15% of the total amount of the thermally modified compound is added to the ball milling fluid to adjust the ball milling modification treatment. After the treatment is completed, the mixture is washed with water and dried to obtain the deterioration regulator.
[0107] In this embodiment, the ball milling speed for the ball milling modification treatment is 1500 r / min, and the ball milling time is 2 h.
[0108] In this embodiment, the silane coupling agent is silane coupling agent KH560; the organic alcohol amine is diethanolamine.
[0109] The specific operation method for the thermal efficiency improvement treatment in this embodiment is as follows:
[0110] The aluminum rod is first heated to 220℃ at a rate of 3℃ / min and held for 15 minutes. Then it is heated to 350℃ at a rate of 5℃ / min and held for 5 minutes. Next, it is cooled to 175℃ at a rate of 4℃ / min and finally cooled to room temperature at a rate of 2℃ / min.
[0111] In this embodiment, the wire blank is further treated with an impregnation solution before cold drawing;
[0112] The specific operating steps are as follows:
[0113] S11: Prepare a sodium silicate solution with a mass fraction of 15% by first mixing sodium silicate and deionized water.
[0114] S12: Add 6 parts of sodium silicate solution to 20 parts of chitosan solution with a mass fraction of 5%, then add 3 parts of sodium nitrate and 2 parts of phosphoric acid solution, stir well to obtain the base agent;
[0115] S13: Add 9 parts of sheet graphene and hydroxyapatite agent and 5 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution;
[0116] S14: Pass the wire rod through the impregnation solution at a speed of 0.6 m / min. The wire rod is impregnated in the impregnation solution at a pressure of 20 MPa and a temperature of 68°C. After impregnation, dry it at 60°C for 40 min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
[0117] The phosphoric acid solution in this embodiment has a mass fraction of 8%.
[0118] The preparation method of the sheet-like graphene-modified hydroxyapatite agent in this embodiment is as follows:
[0119] The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature.
[0120] Add 5 parts of carboxymethyl cellulose to 15 parts of ethanol solvent, then add 8 parts of hydroxyapatite, 5 parts of silica sol and 2 parts of tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite modifier.
[0121] Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 and ball milled at a speed of 1000 r / min for 2 hours. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
[0122] The heat treatment conditions in this embodiment are: heat treatment at 270°C for 30 minutes.
[0123] In step five of this embodiment, the extrusion is carried out at an extrusion temperature of 390°C and an extrusion speed of 0.05 mm / s.
[0124] Example 3.
[0125] This embodiment provides a method for improving the high conductivity of magnesium-aluminum alloy wire, comprising the following steps:
[0126] Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.35%, Cr 0.05%, Si 0.035%, Ti 0.125%, modification modifier 0.15%, and the balance is Al;
[0127] Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for another 15 minutes to obtain the molten liquid.
[0128] Step 3: The molten liquid from Step 2 is refined for 7.5 minutes using a refining gas composed of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:1. The gas flow rate is 1.3 cubic meters per minute and the pressure is 0.125 atm to obtain the refined liquid.
[0129] Step 4: The refining liquid is cast using an upward drawing aluminum rod with a speed of 225 mm / min and a diameter of 31 mm.
[0130] Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm;
[0131] Step Six: The wire blank is then cold-drawn at a deformation rate of 40%. After the process is completed, the magnesium-aluminum alloy wire of the present invention can be obtained.
[0132] The preparation method of the deterioration regulator in this embodiment is as follows:
[0133] S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of 5:1, and then heat-treated at 215℃ for 7.5 min. After that, the mixture is cooled to 48℃ at a rate of 3.5℃ / min, kept at that temperature, and then set aside to obtain the heat-modified compound agent.
[0134] S02: Add 4 parts citric acid and 3 parts sodium sulfate (6% by mass) to 12.5 parts deionized water, then add 1.5 parts silane coupling agent KH560 and 0.50 parts organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry;
[0135] S03: Subsequently, 12.5% of the total amount of the thermally modified compound was added to the ball milling fluid to adjust the ball milling modification treatment. After the treatment was completed, the mixture was washed with water and dried to obtain the deterioration regulator.
[0136] In this embodiment, the ball milling speed for the ball milling modification treatment is 1250 r / min, and the ball milling time is 1.5 h.
[0137] In this embodiment, the silane coupling agent is silane coupling agent KH560; the organic alcohol amine is triethanolamine.
[0138] The specific operation method for the thermal efficiency improvement treatment in this embodiment is as follows:
[0139] The aluminum rod is first heated to 215℃ at a rate of 2℃ / min and held for 12 minutes. Then it is heated to 350℃ at a rate of 4℃ / min and held for 5 minutes. Next, it is cooled to 170℃ at a rate of 3℃ / min and finally cooled to room temperature at a rate of 1.5℃ / min.
[0140] In this embodiment, the wire blank is further treated with an impregnation solution before cold drawing;
[0141] The specific operating steps are as follows:
[0142] S11: Prepare a sodium silicate solution with a mass fraction of 12.5% by first mixing sodium silicate and deionized water.
[0143] S12: Add 5 parts of sodium silicate solution to 17.5 parts of chitosan solution with a mass fraction of 5%, then add 2.5 parts of sodium nitrate and 1.5 parts of phosphoric acid solution, stir evenly to obtain the base agent;
[0144] S13: Add 7 parts of sheet graphene and hydroxyapatite agent and 3.5 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution;
[0145] S14: Pass the wire rod through the impregnation solution at a speed of 0.5 m / min. The wire rod is impregnated in the impregnation solution at a pressure of 15 MPa and a temperature of 66°C. After impregnation, dry the wire rod at 57°C for 35 min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
[0146] The phosphoric acid solution in this embodiment has a mass fraction of 6.5%.
[0147] The preparation method of the sheet-like graphene-modified hydroxyapatite agent in this embodiment is as follows:
[0148] The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature.
[0149] Add 4 parts of carboxymethyl cellulose to 12.5 parts of ethanol solvent, then add 7 parts of hydroxyapatite, 3.5 parts of silica sol and 1.5 parts of tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite modifier;
[0150] Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 and ball milled at a speed of 1000 r / min for 1.5 h. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
[0151] The heat treatment conditions in this embodiment are 265°C for 25 minutes.
[0152] In step five of this embodiment, the extrusion is carried out at an extrusion temperature of 385°C and an extrusion speed of 0.04 mm / s.
[0153] Comparative Example 1.
[0154] Unlike Example 3, no deterioration regulator was added.
[0155] Comparative Example 2.
[0156] Unlike Example 3, cerium oxide was not added in the preparation of the deterioration regulator.
[0157] Comparative Example 3.
[0158] Unlike Example 3, the deterioration regulator was not subjected to heat treatment at 215°C for 7.5 min in its preparation, and was subsequently cooled to 48°C at a rate of 3.5°C / min and held at that temperature.
[0159] Comparative Example 4.
[0160] Unlike Example 3, the preparation of the deterioration regulator did not involve adjusting the ball milling slurry; instead, it was directly ball milled.
[0161] Comparative Example 5.
[0162] Unlike Example 3, no silane coupling agent KH560 and organic alcohol amines were added during the preparation of the ball milling slurry.
[0163] Comparative Example 6.
[0164] Unlike Example 3, no thermal efficiency improvement treatment was used.
[0165] Comparative Example 7.
[0166] Unlike Example 3, in the preparation of the thermal efficiency improvement treatment, the aluminum rod is first heated to 215°C at a rate of 2°C / min, held at that temperature for 12 min, then cooled to 170°C at a rate of 3°C / min, and finally cooled to room temperature at a rate of 1.5°C / min.
[0167] Comparative Example 8.
[0168] Unlike Example 3, in the preparation of the thermal efficiency improvement treatment, the aluminum rod is first heated to 215°C at a rate of 2°C / min and held for 12 min, then heated to 350°C at a rate of 4°C / min and held for 5 min, and then cooled to room temperature at a rate of 1.5°C / min.
[0169] Comparative Example 9.
[0170] Unlike Example 3, this one did not use the impregnation and conditioning solution for improvement treatment.
[0171] Comparative Example 10.
[0172] The difference from Example 3 is the specific method of the improved treatment by soaking in the soaking solution: the soaking solution was not used for soaking in the soaking solution, the soaking pressure was 15 MPa, and the soaking temperature was 66°C.
[0173] Comparative Example 11.
[0174] Unlike Example 3, sodium silicate solution and sodium nitrate were not added to the base agent in the improved impregnation treatment.
[0175] Comparative Example 12.
[0176] Unlike Example 3, the impregnation solution in the improved impregnation treatment did not contain flake graphene and hydroxyapatite agents.
[0177] The products of Examples 1-3 and Comparative Examples 1-12 were subjected to performance tests. Simultaneously, the products were placed in a 2% hydrochloric acid mist for 6 hours, and their acid resistance was tested. The test results are as follows.
[0178]
[0179] As can be seen from Comparative Examples 1-12 and Examples 1-3;
[0180] The product in Example 3 has excellent steady-state creep rate and excellent electrical conductivity. The electrical conductivity and high-temperature creep resistance can be improved in a coordinated manner. In addition, the product has excellent performance stability under acid corrosion conditions.
[0181] As can be seen from Comparative Examples 1-5 and Example 3, the performance of the product deteriorated significantly when no modification modifier was added in the present invention. In addition, the product performance deteriorated in the preparation of the modification modifier because cerium oxide was not added, the product was not subjected to heat treatment at 215°C for 7.5 min and then cooled to 48°C at a rate of 3.5°C / min, the product was not kept at the same temperature, the product was not prepared by adjusting the ball milling fluid, the product was directly ball milled, and the product performance deteriorated in the preparation of the ball milling fluid. Only the modification modifier prepared by the method of the present invention showed the most significant performance effect.
[0182] The inventors of this invention have also discovered that among the ball milling fluids, only the ball milling fluid products prepared using the raw materials of this invention exhibit the most significant performance effects.
[0183] As can be seen from Comparative Examples 6-8 and Example 3, the performance of the products tends to deteriorate depending on whether thermal efficiency improvement treatment is used or the specific conditions of thermal efficiency improvement treatment are different.
[0184] As can be seen from Comparative Examples 9-12 and Example 3, the performance of the product deteriorated significantly when the impregnation and conditioning treatment was not used. The performance of the product deteriorated with different specific methods of impregnation and conditioning treatment. It was also found that the performance of the product deteriorated more significantly when the flake graphene and hydroxyapatite agent were not added to the impregnation and conditioning solution.
[0185] Comparative Examples 1, 6, 9 and 3 show that without the addition of a degradation modifier, without thermal efficiency improvement treatment, and without impregnation improvement treatment with a soaking solution, the product performance tends to deteriorate significantly. Only by using all three in combination and working together can the product performance be most significantly improved.
[0186] This invention further explores the product performance through the preparation of sheet-like graphene-modified hydroxyapatite agent;
[0187] Experimental Example 1.
[0188] Same as Example 3, except that hydroxyapatite was not added in the preparation of the sheet graphene-blended hydroxyapatite agent.
[0189] Experimental Example 2.
[0190] Same as Example 3, except that no silica sol was added in the preparation of the sheet graphene-hydroxyapatite agent.
[0191] Experimental Example 3.
[0192] Same as Example 3, except that in the preparation of the sheet graphene-hydroxyapatite agent, sheet talc powder is used instead of sheet graphene.
[0193] Experimental Example 4.
[0194] Similar to Example 3, except that in the treatment of sheet graphene cooled to room temperature, sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred evenly, then washed with water and dried instead of undergoing heat treatment.
[0195] Experimental Example 5.
[0196] Similar to Example 3, except that the sheet graphene cooled to room temperature and the hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 for ball milling at a speed of 1000 r / min for 1.5 h. After ball milling, the steps of washing and drying were replaced by mixing the sheet graphene cooled to room temperature and the hydroxyapatite modifier at a weight ratio of 2:9, stirring evenly, and then washing and drying with water. Ball milling was not used.
[0197] The performance test results of Examples 1-5 are as follows:
[0198]
[0199] As can be seen from Examples 1-5, the performance of the product deteriorated significantly when hydroxyapatite was not added during the preparation of the sheet graphene-blended hydroxyapatite agent. Secondly, the performance also deteriorated significantly when sheet graphene was replaced with sheet talc powder during the preparation of the sheet graphene-blended hydroxyapatite agent. Furthermore, the performance of the product deteriorated when heat treatment was not performed, ball milling was not used, or silica sol was not added during the preparation of the sheet graphene-blended hydroxyapatite agent. Only the sheet graphene-blended hydroxyapatite agent prepared by the method of the present invention showed the most significant performance effect. The effects of other methods were not as significant as those of the present invention.
[0200] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0201] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for improving the high conductivity of magnesium-aluminum alloy wire, characterized in that, Includes the following steps: Step 1: Weigh the raw materials according to the following weight percentages: Mg 3.2~3.5%, Cr 0.04~0.06%, Si 0.03~0.04%, Ti 0.10~0.15%, modification modifier 0.10~0.20%, and the balance is Al; Step 2: The Mg, Cr, and Si raw materials from Step 1 are fed into a melting furnace for melting. The mixture is stirred every 15 minutes. Then Ti and a modifier are added, and the melting continues for 10-20 minutes to obtain the molten liquid. Step 3: The molten liquid from Step 2 is refined for 5-10 minutes using a refining gas composed of nitrogen, chlorine, and carbon monoxide in a weight ratio of 3:1:
1. The gas flow rate is 1.2-1.4 cubic meters per minute, and the pressure is 0.12-0.13 atm to obtain the refined liquid. Step 4: The refining liquid is cast using an upward drawing method. The upward drawing speed of the aluminum rod is 220~230mm / min, and the diameter of the upward drawing aluminum rod is 30~32mm. Step 5: The aluminum rod from Step 4 is heat-treated for improvement, and then extruded under extrusion conditions to form a wire blank with a diameter of 10mm; Step 6: The wire blank is then cold-drawn at a deformation rate of 40%. After the process is completed, magnesium-aluminum alloy wire is obtained. The method for preparing the deterioration regulator is as follows: S01: Lanthanum trioxide and cerium oxide are mixed evenly at a weight ratio of (4~6):
1. Then, the mixture is first heat-treated at 210~220℃ for 5~10 min, and then cooled to 48℃ at a rate of 2~5℃ / min. The mixture is then kept at this temperature for later use to obtain the heat-modified compound. SO2: Add 3-5 parts of citric acid and 2-4 parts of sodium sulfate (6% by mass) to 10-15 parts of deionized water, then add 1-2 parts of silane coupling agent and 0.45-0.55 parts of organic alcohol amine, stir evenly to obtain the adjusted ball milling slurry; S03: Subsequently, 10-15% of the total amount of the thermally modified compound is added to the ball milling slurry to adjust the ball milling modification treatment. After the treatment is completed, the mixture is washed with water and dried to obtain the deterioration regulator. The specific operation method for the thermal efficiency improvement treatment is as follows: First, heat the aluminum rod to 210-220℃ at a rate of 1-3℃ / min and hold for 10-15 minutes. Then, heat it to 350℃ at a rate of 3-5℃ / min and hold for 5 minutes. Next, cool it to 165-175℃ at a rate of 2-4℃ / min. Finally, cool it to room temperature at a rate of 1-2℃ / min.
2. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 1, characterized in that, The ball milling speed for ball milling modification treatment is adjusted to 1000~1500 r / min, and the ball milling time is 1~2 h.
3. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 2, characterized in that, The silane coupling agent is silane coupling agent KH560; the organic alcohol amine is one or more combinations of triethanolamine, diethanolamine, and ethanolamine.
4. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 1, characterized in that, Before the re-cold drawing process, the wire blank is further treated by impregnation with a soaking solution. The specific operating steps are as follows: S11: Prepare a sodium silicate solution with a mass fraction of 10-15% by first mixing sodium silicate and deionized water; S12: Add 4-6 parts of sodium silicate solution to 15-20 parts of 5% chitosan solution, then add 2-3 parts of sodium nitrate and 1-2 parts of phosphoric acid solution, stir well to obtain the base agent; S13: Add 5-9 parts of sheet graphene and hydroxyapatite agent and 2-5 parts of sodium dodecylbenzenesulfonate to the base conditioner and stir thoroughly to obtain the impregnation solution; S14: Pass the wire rod through the impregnation solution at a speed of 0.4~0.6m / min, and impregnate it in the impregnation solution at a pressure of 10~20MPa and a temperature of 65~68℃. After impregnation, dry it at 55~60℃ for 30~40min. Then, purge the wire rod with nitrogen until the surface of the wire rod is clean.
5. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 4, characterized in that, The phosphoric acid solution has a mass fraction of 5-8%.
6. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 5, characterized in that, The preparation method of the sheet-like graphene-modified hydroxyapatite agent is as follows: The sheet graphene was added to a 2% hydrochloric acid solution at a weight ratio of 1:5 and stirred until homogeneous. Then it was washed with water, dried, heat-treated, and then air-cooled to room temperature. Add 3-5 parts of carboxymethyl cellulose to 10-15 parts of ethanol solvent, then add 6-8 parts of hydroxyapatite, 2-5 parts of silica sol and 1-2 parts of tetrabutyl titanate, stir thoroughly to obtain hydroxyapatite regulator. Flake graphene cooled to room temperature and hydroxyapatite modifier were fed into a ball mill at a weight ratio of 9:2 and ball milled at a speed of 1000 r / min for 1-2 hours. After ball milling, the mixture was washed with water and dried to obtain flake graphene and hydroxyapatite modifier.
7. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 6, characterized in that, The heat treatment conditions are 260~270℃ for 20~30 minutes.
8. The method for improving the high conductivity of magnesium-aluminum alloy wire according to claim 7, characterized in that, In step five, the extrusion is carried out at an extrusion temperature of 380~390°C and an extrusion speed of 0.03~0.05mm / s.
Citation Information
Patent Citations
Method for the refining and structure modification of al-mg-si alloys
CA2866094A1
Gravity casting process of aluminum magnesium alloy explosion-proof box
CN115386749A